“It’s just very natural” – interpersonal knowledge as a didactical device in guided classroom conversations in religious education - Øystein Lund Johannessen (Nordidactica: Journal of Humanities and Social Science Education, 2014)
This article investigates how teachers in religious education (RE) think and act as professionals while working with differences in religious and philosophy of life experiences and beliefs in class and trying to do this in respectful and inclusive ways. It analyses data from two research projects that were carried out in lower secondary school in Norway. The main research question is: What is the relationship between teachers’ contextual knowledge and knowledge of the child and how do these two dimensions of professional knowledge interact when religious education teachers try to strike a good balance between inclusion and productive learning in their teaching practice? The data analysed were drawn from three different data sets featuring three Norwegian religious education-teachers. The research was part of the EU-funded “REDCo”-project and the “Religious education and diversity” - project [“ROM”] funded by the Norwegian Research Council. The interviewees emphasized the potential of the religious education subject to contribute to a wider tolerance for difference and to support individual students in their identity management. The analysis shows, however, that considerable contextual awareness - of the classroom and of the local community - is needed to realize this potential. It also shows the importance of interpersonal knowledge between the teacher and each student if contextual awareness is to be effective in terms of inclusion, participation, wellbeing and good learning outcomes for all students.